Exploring social patterns of participation in university-entrance level mathematics in England - Noyes, Andrew (Taylor and Francis Group, 2009)
In recent years in England there has been considerable attention given to a range of apparent crises in mathematics education, one of which has been the long term decline of participation in university-entrance level (Advanced or A) mathematics. Given the negative impact upon mathematics participation of Curriculum 2000, together with the government’s emphasis on Science Technology Engineering and Mathematics (STEM) subjects, the political intent to increase participation in Advanced level mathematics is clear. This paper uses the National Pupil Database (NPD) to develop a descriptive statistical account of how completion of Advanced level mathematics varies along the social axes of SES, ethnicity and gender. The process of working with the NPD is discussed in some depth in order to clarify the processes involved in this type of quantitative analysis and to illustrate how this analysis can be used to raise questions about who is doing what mathematics in the post-16 age-range.